The effects of feedback on students' achievement goals: Interaction between reference of comparison and regulatory focus. (June 2017) - Shin, Jongho; Lee, You-kyung; Seo, Eunjin
Abstract: The purpose of the present study was to examine the effect of reference of comparison (i.e., self-referential vs. normative) and regulatory focus (i.e., promotion vs. prevention) on students' subsequent achievement goals. We hypothesized that the negative effect of normative feedback on students' achievement goals would decrease or disappear when the feedback is promotion focused. The results from an experimental study ( n  = 155 sixth and seventh graders) supported the hypothesis. In general, normative feedback led students to more endorsement of performance-approach and performance-avoidance goals as compared to self-referential feedback. When students received promotion-focused feedback, however, normative feedback did not significantly lead to performance goal endorsement. Regarding mastery goal adoption, none of the feedback types had any significant effect on it. The results provide implications about how to buffer the detrimental effects of normative feedback on performance goal endorsement using promotion-focused feedback. Highlights: We examine comparison reference and regulatory focus effects on achievement goals. Normative feedback leads to more endorsement of performance goals. Promotion-focused feedback buffers the detrimental effect of normative feedback. Feedback on progress should be provided under social comparison situation.